Tomato diseases, quality, yield and pesticide use - Berlin, Anna; Eitrem, Sofia (2005)
Nicaraguan farmers have for a long time struggled with tomato production. The primary problem has been Begomovirus infection, which devastated the tomato production in the country in the 1990's. In the battle against the Begomovirus other problems in the native tomato production have been neglected. The overall goal with these projects was to identify common tomato diseases and to evaluate their effect on yield and quality of the tomato fruits at different nitrogen levels. This report contains two separate theses (chapter 2 and 3). The results of the studies are based on the same field experiments. To increase the understanding about local farming conditions (chapter 1), interviews were made at two locations. During the interviews the farmers were asked questions about the farms, their production and pesticide use. Today, the farmers overuse chemical products to control different pests. The Nicaraguan farmers in general have a strong belief that pesticides are the solution of all their agricultural problems.